A 36-Year Record of Rock Avalanches in the Saint Elias Mountains of Alaska, With Implications for Future Hazards - Bessette-Kirton, Erin K.; Coe, Jeffrey A. (Frontiers in Earth Science, 2020)
Glacial retreat and mountain-permafrost degradation resulting from rising global temperatures have the potential to impact the frequency and magnitude of landslides in glaciated environments. Several recent events, including the 2015 Taan Fiord rock avalanche, which triggered a tsunami with one of the highest wave runups ever recorded, have called attention to the hazards posed by landslides in regions like southern Alaska. In the Saint Elias Mountains, the presence of weak sedimentary and metamorphic rocks and active uplift resulting from the collision of the Yakutat and North American tectonic plates create landslide-prone conditions. To differentiate between the typical frequency of landsliding resulting from the geologic and tectonic setting of this region, and landslide processes that may be accelerated due to changes in climate, we used Landsat imagery to create an inventory of rock avalanches in a 3700 km2 area of the Saint Elias Mountains. During the period from 1984-2019, we identified 220 rock avalanches with a mean recurrence interval of 60 days. We compared our landslide inventory with a catalog of M ≥ 4 earthquakes to identify potential coseismic events, but only found three possible earthquake-triggered rock avalanches. We observed a distinct temporal cluster of 41 rock avalanches from 2013 through 2016 that correlated with above average air temperatures (including the three warmest years on record in Alaska, 2014-2016); this cluster was similar to a temporal cluster of recent rock avalanches in nearby Glacier Bay National Park and Preserve. The majority of rock avalanches initiated from bedrock ridges in probable permafrost zones, suggesting that ice loss due to permafrost degradation, as opposed to glacial thinning, could be a dominant factor contributing to rock-slope failures in the high elevation areas of the Saint Elias Mountains. Although earthquake-triggered landslides have episodically occurred in southern Alaska, evidence from our study suggests that area-normalized rates of non-coseismic rock avalanches were greater during the period from 1964 to 2019, and that the frequency of these events will continue to increase as the climate continues to warm. These findings highlight the need for hazard assessments in Alaska that address changes in landslide patterns related to climate change.